2019
DOI: 10.1002/ddr.21512
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the antibacterial and antifungal activity of thiolated naphthoquinones

Abstract: The WHO has stated that antibiotic resistance is escalating to perilously high levels globally and that traditional therapies of antimicrobial drugs are futile against infections caused by resistant microorganisms. Novel antimicrobial drugs are therefore required. We report in this study on the inhibitory activity of the 1,4‐naphthoquinone‐2,3‐bis‐sulfides and 1,4‐naphthoquinone sulfides against two bacteria and a fungus to determine their antimicrobial properties. The 1,4‐naphthoquinone sulfides have potent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…In contrast, Wellington et al (2019) studied sulfide-substituted 1,4-NQ derivatives and reported MIC 50 levels for S. aureus of 7.8 μg/mL, whereas it was 23.4 μg/mL for C. albicans . The MIC 50 value for Candida spp was decreased to 2–4 μg/mL by the incorporation of chlorine subgroups in 5,8-dihydroxy-1,4-NQ [ 2 , 7 ]. These MIC 50 values even decreased to <0.6 μg/mL with the substitution of two hydroxyl subgroups to 1,4-NQ, showing that the inclusion of hydroxyl side groups in the same compound produced a stronger antifungal effect than the previously synthesized derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Wellington et al (2019) studied sulfide-substituted 1,4-NQ derivatives and reported MIC 50 levels for S. aureus of 7.8 μg/mL, whereas it was 23.4 μg/mL for C. albicans . The MIC 50 value for Candida spp was decreased to 2–4 μg/mL by the incorporation of chlorine subgroups in 5,8-dihydroxy-1,4-NQ [ 2 , 7 ]. These MIC 50 values even decreased to <0.6 μg/mL with the substitution of two hydroxyl subgroups to 1,4-NQ, showing that the inclusion of hydroxyl side groups in the same compound produced a stronger antifungal effect than the previously synthesized derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…The central molecule of naphthalene consists of a benzene moiety fully conjugated to another cyclic diketone ring. Due to these properties, 1,4-NQs are produced by various horticultural plants; in addition, some fungi and animals [ 2 ] have antibacterial [ 3 ], antimalarial [ 4 ] antiparasitic [ 5 ], antiviral, and antifungal activities [ 6 , 7 , 8 ] and thus have long been used in traditional medicine [ 9 , 10 ]. Moreover, the substitution of some side groups to NQs, such as hydroxyl, methyl, nitrogen, sulfur, halide, phenylamino-phenylthio, sulfur, etc., has conferred additional remarkable biological activities to the molecule [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal activity of 1,4-naphthoquinone sulfides showed decreased (23.4 mg/ml) in comparison to Amphotericin B (31.3 mg/ml) against C. albicans . [ 63 ] The efficacy of lawsone (2-hydroxy-1,4-naphthoquinone)-based compound was found more significant in comparison to conventional antibiotics against methicillin-resistant S. aureus (MRSA) in vitro as well as in vivo . [ 64 ]…”
Section: N Apthoquinonesmentioning
confidence: 99%
“…6,7 Accordingly, an increasing number of aminated and/or thiolated quinones have been prepared, leading to the discovery of novel bioactive products. [8][9][10] Mono-and/or disubstituted quinone motifs, in particular, are present in various pharmacologically related molecules, including those used as lead molecules for Leber's Hereditary Optic Neuropathy (LHON), 11 anticancer, 12 antibacterial, 13,14 antifungal, 15,16 antiHIV, 17 and antimalarial therapy. 18 It is worth noting that some 1,4-quinones have also found use as functional ligands for transition metals.…”
Section: Introductionmentioning
confidence: 99%